Endoxifen for behavioral and psychological symptoms of dementia and hypersexuality - Sagar Karia; Prachi Lajurkar (Journal of Geriatric Mental Health)
The behavioral and psychological symptoms of dementia (BPSD) are neuropsychiatric symptoms that accompany the syndrome of dementia. Research indicates that increased protein kinase C (PKC) signaling is one of the earliest changes observed in the pathology of Alzheimer’s disease dementia. Endoxifen a potent inhibitor of the PKC signaling pathway has demonstrated benefits in controlling acute bipolar mania, impulsivity, and borderline personality disorder. Here, we present the case of a patient with BPSD and hypersexuality managed with endoxifen 8 mg in addition to other medications for BPSD. Adjuvant treatment with endoxifen was efficacious in controlling severe behavioral symptoms and hypersexual behavior, with no adverse effects.